Oral laser application - Moritz, Andreas; Goharkhay, K.; Schoop, U.; Strassl, M.; Verheyen, P.; Walsh, L. J.; Wernisch, J.; Wintner, E.; Beer, F.; Blum, Romain; Maiorana, Carlo; Peschek, Antonia; et al. (Berlin : Quintessenz Verlags-GmbH, 2006)
Offers a comprehensive account of all conventional indications for laser-assisted dentistry, including cavity preparation, endodontics, and periodontal therapy, as well as recent advancements such as laser-assisted bleaching, soft laser applications, and the treatment of hypersensitive cervical areas. For each indication, detailed instructions on the use of the laser are provided in both text and illustrations to allow even novices to make successful, responsible, and immediate use of this innovative technology. In addition, each chapter presents its topic in the context of the underlying scientific concepts and a thorough and up-to-date review of the extant literature. The book also features in-depth discussion of all available wavelengths and their specific applications to guide readers in the purchase of a new laser system as well as extensive case reports to demonstrate achievable therapeutic outcomes and allow readers to compare their results with those of other users. Oral Laser Application is an invaluable guide for all clinicians currently using or wishing to integrate laser-assisted dentistry in their practice.
The Nature, Properties and Sources of Light – E. Wintner, M. StraBl -- 2. Laser Safety – F. Beer, M. StraBl, J. Wernisch -- 3. Cavity Preparation – A. Moritz, U. Schoop, M. StraBl, E. Wintner -- 4. Photopolymerization – P. Verheyen, A. Moritz, L.J. Walsh -- 5. Caries Prevention – K. Goharkhay, A. Moritz -- 6. Lasers in Endodontics – A. Moritz, U. Schoop -- 7. Pulp Capping and Pulpotomy in Permanent and Primary Teeth – A. Pescheck, A. Moritz -- 8. Laser-Assisted Periodontal Therapy – U. Schoop -- 9. Dentin Hypersensitivity – K. Goharkhay, J. Wernisch, A. Moritz -- 10. Laser-Assisted Bleaching – P. Verheyen, L.J. Walsh, J. Wernisch, U. Schoop, A. Moritz -- 11. Laser-Atlas Surgery – F. Beer -- 12. Photoactivated Disinfection (PAD) – P. Verheyen, R. Blum, K. Goharkhay, L.J. Walsh -- 13. Low Level Laser Therapy (LLLT) – L.J. Walsh, K. Goharkhay, P. Verheyen, A. Moritz
Keywords: LÁSER-ODONTOLOGÍA; CAVIDAD DENTARIA; CARIES DENTARIA